Food security and economic growth in developing countries - Abdul Manap, Nur Marina (2015)
Food security is defined as a situation in which all people at all times have both physical and economic access to sufficient food to meet their dietary need for a productive and healthy life. Food security problem is a crucial issue for national development, poverty alleviation and becomes a global issue due to the Millennium Development Goals (MDG) target by 2015. Food security problem occurs when there is a sudden drop in the ability to produce or have access enough food to maintain a good nutritional status and it is known as transitory food deficit. The transitory food deficit is caused by two important reasons, where first is caused by the fluctuation in food production which is caused by lack of irrigation, fertilizers consumption and climatic problem that are faced by dry-land irrigation areas. Secondly, it is caused by the world food crisis that gives a huge impact for dry-land developing countries. In order to overcome food security problem in dry-land developing countries, United States Agency International Development (USAID) and Food and Agriculture Organization (FAO) have introduce several plans necessary for achieving food security and it is known as availability, accessibility, utilization and stability. Moreover, food security is very important to enhance economic growth. The objective of the study is to examine the impact of food input resources on food production in dry-land developing countries. Besides that, this research also investigates the role of food security dimension for food security achievement and the impact of food security on economic growth in dry-land developing countries. This research employs static panel data by using random and fixed effects analysis for the first and second objectives. Besides that, the estimation for the impact of food security and economic growth has used dynamic panel data analysis, which adopts Generalized Method of Moments (GMM) for the third objective of the analysis. The finding of this research shows that land irrigation has a positively significant impact on the food production in dry-land developing countries. However, fertilizer consumption and climate change do not give significant impact on food production. Besides that, the finding for the dimension of food security has found that the policy that has been built by USAID is more appropriate which involves food availability, accessibility and utilization compared to FAO policy where this organization has added food stability in the policy and the result does not give significant impact on food security in dry-land developing countries. Finally, food security positively gives an impact to economic growth in dry-land developing countries. Besides that, reduction in poverty with better food security will increase economic growth. Additionally, life expectancy and total employment rate with better food security positively enhance economic growth in dry-land developing countries.